(untitled) (Medical Forum Monthly, 2024)
Objective: To evaluate the role of complement C3, C4 levels, Immunoglobulin E, eosinophil counts, platelets counts, hemoglobin levels and C-reactive protein (CRP) in children with asthma. Study Design: This was a case control study. Place and Duration of Study: This study was conducted at the Department of Pediatric Medicine, the Institute of Child Health, Multan and Pediatrics Department, Services Hospital, Lahore, Pakistan from September 2018 to February 2019. Materials and Methods: A total of 160 children (80 cases and 80 controls) aged up to 16 years were included. Cases were diagnosed accompanying asthma while controls were healthy volunteers. Chi square test was adopted for comparing qualitative variables while t test was used for quantitative variables. P value less than or equal to 0.05 was taken as of statistical significance. Results: Out of a total of 160 children, when cases and controls were compared, there was no statistical significance in terms of gender distribution (p = 0.423) or age (p = 0.066) in between cases and controls levels of CRP (p < 0.0001), C3 (p < 0.0001), Total IgE (p < 0.0001), hemoglobin (p < 0.0001) and eosinophi count (p < 0.0001) were significantly raised cases as compared to controls while C4 levels were noted to be significantly reduced in cases as compared to controls (p < 0.0001). Conclusion: Children with asthma were found to have significantly raised C3, total IgE, eosinophil count and CRP levels but significantly reduced levels of C4 and hemoglobin and C4. These parameters could be used to mark severity as well as the prognosis of asthma in children.